INBOUND TOURISM: THE IMPACT OF FDI, ECONOMIC WELLBEING, AND RELIGIOUS SIMILARITY OF COUNTRIES ON THE INFLOW OF FOREIGN VISITORS (Лучшие интеллектуальные исследования, 2025)
This study investigates the factors influencing international tourist inflow across 68 randomly selected countries using cross-sectional data for the year 2022. The analysis focuses on the effects of foreign direct investment (FDI) inflow, real GDP, and religious similarity on the number of international tourist arrivals. Two regression models are developed: Model 1 examines the bivariate relationship between tourist inflow and FDI, while Model 2 incorporates real GDP and a religion-based dummy variable as additional explanatory variables. Results from Model 1 reveal a statistically significant positive relationship, where a 1% increase in FDI corresponds to a 0.333% increase in tourist inflow. However, in Model 2, the coefficient for FDI becomes statistically insignificant due to multicollinearity with real GDP, which itself exhibits a significant positive effect on tourism. The religion variable, used as a proxy for cultural similarity, shows a negative but insignificant effect. The study concludes that while FDI is initially associated with greater tourist inflows, its effect is mediated by broader economic activity, as captured by real GDP. The findings emphasize the importance of economic conditions over isolated investment flows in driving international tourism.